Enhancing Forming Limits by Using a Magnetorheological Fluid as Active Fluid Medium for Hydroforming - Rösel, Sebastian; Merklein, Marion (Steel research international: Special Edition: 10th International Conference on Technology of Plasticity, 2011)
The automobile industry has to preserve commodities by light weight constructions. It is to the forming technology to overcome the challenges of forming high complex part geometries, by offering more flexible forming technologies e.g. hydroforming, which are cost efficient and can utilize the whole formability of the used materials. One active deviance, which has prevented the application of hydroforming of blanks In serial production, is the sealing of the cavity In the flange area. To Insure a complete sealing, it Is necessary to remain below a defined ratio between cavity pressure and contact pressure In the flange area, which Is restricting the process window. This experimental work focuses on the Influence of the magnetorheological fluid Basonetic 5030 on the sealing ratio compared to mineral oil shell tellus 100. Experiments are carried out at different cavity and contact pressures with the media mentioned above. Additionally a defined magnetic flux density Is applied to the magnetorheological fluid In the flange area to Increase its viscosity. Afterwards cups are drawn with DC04 of a sheet thickness of 1 mm and the resulting cup geometries are measured. Various geometric parameters are compared to each other to identify the process latitudes and the possible process parameters. © 2011 Wiley-VCH Verlag GmbH & Co. KGaA. Weinheim.
LFT Import::2019-08-05 (1650)
Keywords: Forming processes; Hydroforming; Magnetorheological fluid (MRF); Sheet metal